Beispiel Nr: 12
$ \text{Gegeben:} \text{Gerade 1: } \vec{x} =\left( \begin{array}{c} a1 \\ a2 \\ a3 \\ \end{array} \right) + \lambda \left( \begin{array}{c} b1 \\ b2 \\ b3 \\ \end{array} \right) \\ \text{Gerade 2: } \vec{x} =\left( \begin{array}{c} c1 \\ c2 \\ c3 \\ \end{array} \right) + \sigma \left( \begin{array}{c} d1 \\ d2 \\ d3 \\ \end{array} \right) \\ \text{Gesucht:} \text{Die Lage der Geraden zueinander.} \\ \\ \textbf{Gegeben:} \\ \text{Gerade 1: } \vec{x} =\left( \begin{array}{c} 1 \\ 0 \\ 3 \\ \end{array} \right) + \lambda \left( \begin{array}{c} 2 \\ -3 \\ 1 \\ \end{array} \right) \\ \text{Gerade 2: } \vec{x} =\left( \begin{array}{c} 4 \\ -4 \\ -2 \\ \end{array} \right) + \sigma \left( \begin{array}{c} -4 \\ 6 \\ 2 \\ \end{array} \right) \\ \\ \\ \textbf{Rechnung:} \\ \text{Gerade 1: } \vec{x} =\left( \begin{array}{c} 1 \\ 0 \\ 3 \\ \end{array} \right) + \lambda \left( \begin{array}{c} 2 \\ -3 \\ 1 \\ \end{array} \right) \\ \text{Gerade 2: } \vec{x} =\left( \begin{array}{c} 4 \\ -4 \\ -2 \\ \end{array} \right) + \sigma \left( \begin{array}{c} -4 \\ 6 \\ 2 \\ \end{array} \right) \\ \text{Richtungsvektoren: } \\ \left( \begin{array}{c} 2 \\ -3 \\ 1 \\ \end{array} \right) =k \cdot \left( \begin{array}{c} -4 \\ 6 \\ 2 \\ \end{array} \right) \\ \begin{array}{cccc} 2&=&-4 k& \quad /:-4 \quad \Rightarrow k=-\frac{1}{2} \\ -3&=&+6 k & \quad /:6 \quad \Rightarrow k=-\frac{1}{2} \\ 1&=&+2 k & \quad /:2 \quad \Rightarrow k=\frac{1}{2} \\ \end{array} \\ \\ \Rightarrow \text{Geraden sind nicht parallel} \\ \left( \begin{array}{c} 1 \\ 0 \\ 3 \\ \end{array} \right) + \lambda \left( \begin{array}{c} 2 \\ -3 \\ 1 \\ \end{array} \right) = \left( \begin{array}{c} 4 \\ -4 \\ -2 \\ \end{array} \right) + \sigma \left( \begin{array}{c} -4 \\ 6 \\ 2 \\ \end{array} \right) \\ \begin{array}{cccccc} 1& +2\lambda &=& 4& -4\sigma& \quad /-1 \quad /+4 \sigma\\ 0& -3\lambda &=& -4& +6 \sigma& \quad /-0 \quad /-6 \sigma\\ 3& +1\lambda &=& -2& +2 \sigma& \quad /-3 \quad /-2 \sigma\\ \end{array} \\ \\I \qquad 2 \lambda +4 \sigma =3\\ II \qquad -3 \lambda -6 \sigma = -4 \\ III \qquad 1 \lambda +2 \sigma = -5 \\ \\ \text{Aus 2 Gleichungen }\lambda \text{ und } \sigma \text{ berechnen } \\ I \qquad 2 \lambda +4 \sigma =3 \qquad / \cdot\left(-3\right)\\ II \qquad -3 \lambda -6 \sigma = -4 \qquad / \cdot\left(-2\right)\\ I \qquad -6 \lambda -12 \sigma =-9\\ II \qquad 6 \lambda +12 \sigma = 8 \\ \text{I + II}\\ I \qquad -6 \lambda +6 \lambda-12 \sigma +12 \sigma =-9 +8\\ 0 \sigma = -1 \qquad /:0 \\ \sigma = \frac{-1}{0} \\ \sigma=-∞ \\ \sigma \text{ in I}\\ I \qquad -6 \lambda -12 \cdot \left(-∞\right) =-9 \\ -6 \lambda +∞ =-9 \qquad / -∞ \\ -6 \lambda =-9 -∞ \\ -6 \lambda =-∞ \qquad / :\left(-6\right) \\ \lambda = \frac{-∞}{-6} \\ \lambda=∞ \\ \lambda \text{ und } \sigma \text{ in die verbleibende Gleichung einsetzen} \\ III \quad 3+∞\cdot1=-2-∞\cdot2 \\ ∞=-∞ \\ \text{Geraden sind windschief} \\ $